The place of professional learning groups in the induction of in-service teacher educators : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Adult Education at Massey University, Palmerston North, New Zealand - Lancaster, Doris (Massey University, 2009)
In New Zealand In-service Teacher Educators (ISTEs) provide professional development for teachers, principals and management in Early Childhood Centres and Schools. ISTEs have been teachers or principals themselves. However, the role of ISTE is different to that of a teacher or principal. There are varied practices throughout New Zealand relating to the induction of ISTEs. The research of Trowler and Knight (1999) concluded that educators required support in gaining explicit knowledge about their new professional role and a process was required to enable this learning to take place. This study investigated how the use of professional learning groups (PLGs) supported the professional learning of five new ISTEs and also examined the perspectives of three members of the team responsible for implementing the PLGs. A mixed-methods approach was taken with predominantly qualitative and some quantitative information gathered from on-line surveys and semi-structured interviews. Broadly, the study's findings suggested that ISTEs do find the transition into their new role difficult and that the PLGs were a relevant structure to support their professional learning and induction. The findings also identified factors related to the broader area of induction of ISTEs. These were collaboration, observation and feedback related to ISTE practice and the leadership and facilitation of the PLG. This study's findings support research that concluded PLGs had the potential to strengthen professional learning and that there were conditions that were necessary for this to occur. The first was the purpose of the PLG related to the PLG as part of a larger induction structure. The second was what occurred in the PLG including the composition of the PLG and the environment that was necessary within the PLGs for them to be effective. Finally, the findings are presented relating to the ISTEs' and the Implementation Team's perspective on the continuation of the PLGs to support the professional learning of new ISTEs. The findings support research that proposed the transition into new professional roles was stressful and that an induction process that met educators' needs was vital to positively support the transition. The findings culminate in five recommendations and three suggestions for further research.
Keywords: New Zealand; Teachers; In-service training; Professional relationships